Kinerja Manajemen Rantai Pasok dengan Menggunakan Pendekatan Metode Supply Chain Operation Reference (SCOR) - Arief Rakhman; Machfud Machfud; Yandra Arkeman (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Business competition in the automotive world is increasingly hypercompetitive. According to the Motor Vehicle Industry Association, annual purchase of motor vehicles has increased the share of automotive business. However, this increasingly open business condition has not been followed by positive impacts on the corporate profits of PT. XYZ in a span of 5 years. This study measured the performance of the supply chain in PT. XYZ using SCOR model approach. The weighting was calculated using fuzzy AHP and performance assessment matrix. The improved supply chain performance was formulated with the method of Focus Group Discussion (FGD). The measurement results show that the performance of supply chain in PT. XYZ is in the Good category (76%), the effectiveness performance with a value of 85% is in Good category while the efficiency performance is in Average category (68%). Supply chain improvement strategy was formulated with 3 tools: campaign quality, shop floor management, and cost control.Keywords: performance appraisal, SCOR, FGD, Fuzzy AHP